Influence of magnetic field on the mass electrodeposition and investigation of corrosion rate on Ni and Ni-Co alloy - Ebadi, M.; Alias, Y.; Basirun, Wan Jefrey (Chemic Publishing Company, 2009)
The electrodeposition of Ni and Ni-Co alloy from a nickel Watt's solution in the absence and presence of a perpendicular magnetic field applied to the cathode surface produced a depositing layer with fine grain structure. It is found that the mass deposition rate with perpendicular magnetic field was greater than the deposition in the absence of magnetic field. The difference between the mass deposition with the presence of perpendicular magnetic field (4.4T) and the absence of magnetic field was ≈ 0.08-1.22 mg cm-2 min-1, if the current was 62 mA cm-2. The deposited layers have been characterized with scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive X-ray (EDX) and electrochemistry corrosion evolution with EIS and Tafel plots.